Long-term exposure to air pollution and mortality in the Danish population a nationwide study. (November 2020) - Raaschou-Nielsen, Ole; Thorsteinson, Erla; Antonsen, Sussie; Holst, Gitte J; Sigsgaard, Torben; Geels, Camilla; Frohn, Lise M; Christensen, Jesper H; Brandt, Jørgen; Pedersen, Carsten B; Hvidtfeldt, Ulla A.
Abstract: Background: Studies have shown higher mortality in association with exposure to air pollution. We investigated this association with focus on differences between socioeconomic groups. Methods: We included all Danes born between 1921 and 1985 aged 30–85 years from 1991 to 2015 ( N = 4, 401, 348). We applied a nested case-control design and identified those who died during follow-up and selected five controls per case. We modelled NO2, fine particulate matter (PM2·5 ), black carbon (BC) particles, and ozone (O3 ) as five-year average concentrations at the residential addresses of 672, 895 all natural cause mortality cases and 3, 426, 533 controls in conditional logistic regression with adjustment for individual and neighbourhood level socio-demographic variables. Findings: In single pollutant models, a 10 μg/m 3 (BC: 1 μg/m 3 ) increase in NO2, PM2·5, BC, and O3 was associated with natural cause mortality rate ratios (MRR) of 1·05 (95% confidence interval 1·04–1·06), 1·08 (1·04–1·13), 1·05 (1·02–1·08), and 0·96 (0·95–0·97), respectively. The patterns were similar for respiratory disease and lung cancer mortality. O3 was associated with higher risk of CVD mortality. The rate differences for a unit increase in PM2·5, NO2, and BC were largest among those with the lowest income; this pattern was not detected when considering the relative risk measure, MRR. Interpretation: Long-term concentration of air pollution at the residence was associated with higher natural cause mortality in the Danish population and the strength of the association differed by socioeconomic group. We recommend that future studies express socioeconomic differences in absolute rather than relative risk.